Modeling Technology Acceptance for Agribusiness Education and Practices in East Java - Firza Prima Aditiawan; Akhmad Fauzi; Mubarokah; I Gede Susrama (Postgraduate, University of Mataram, 2025)
This study develops and validates a model for understanding technology acceptance and use in the agribusiness sector of East Java, Indonesia, using the Unified Theory of Acceptance and Use of Technology (UTAUT) as the foundation. The research analyzed Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention, Use Behavior, Techno Skepticism, and Local Wisdom with data from 207 farmers in Pasuruan Regency, applying PLS-SEM. Results showed that Performance Expectancy and Effort Expectancy were the strongest predictors of Behavioral Intention, while Local Wisdom significantly moderated the relationship between intention and use. Techno Skepticism had a negative effect on intention. The extended UTAUT model thus provides a context-specific framework for agribusiness in developing countries. These findings offer practical implications for education, training, and agricultural policy by aligning digital innovation with local socio-cultural realities.